2019
DOI: 10.1002/adsc.201900612
|View full text |Cite
|
Sign up to set email alerts
|

Domino C−S/C−N Bond Formation Using Well‐Defined Copper‐Phosphine Complex Catalyst: Divergent Approach to 3‐Sulfenylated Indoles

Abstract: A protocol was developed for the synthesis of 3-thioindoles in good-to-excellent yields involving sulfenylation between 2-nitrocinnamaldehydes and various thiols using a well-defined copper(I)-phosphine complex catalyst. This unconventional divergent approach involves in situ generation of indoles via domino CÀ S/CÀ N bond formation initiated by sulfa-Michael addition followed by intramolecular N-heteroannulation. This protocol shows good chemoselectivity and broad substrate scope. To briefly demonstrate the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In 2019, Lee et al carried out heteroannulation of 2-nitrocinnamaldehyde 56 with thiols 57 for direct construction of 3thioindoles 58 with the aid of Cu(I)-phosphene complex. [71] The reaction showed good tolerance towards 2-nitrocinnamaldehydes and a range of alkyl, aryl, heteroaryl substituted thiol systems (61-97 % yield). Under similar reaction conditions the use of o-nitrochalcones 59 instead of nitrocinnamaldehyde 56 delivered 2-benzoyl-3-sulfenylated indoles 60 in good yields.…”
Section: Annulations Involving O-nitrochalcones/o-nitrocinnamaldehydesmentioning
confidence: 92%
See 1 more Smart Citation
“…In 2019, Lee et al carried out heteroannulation of 2-nitrocinnamaldehyde 56 with thiols 57 for direct construction of 3thioindoles 58 with the aid of Cu(I)-phosphene complex. [71] The reaction showed good tolerance towards 2-nitrocinnamaldehydes and a range of alkyl, aryl, heteroaryl substituted thiol systems (61-97 % yield). Under similar reaction conditions the use of o-nitrochalcones 59 instead of nitrocinnamaldehyde 56 delivered 2-benzoyl-3-sulfenylated indoles 60 in good yields.…”
Section: Annulations Involving O-nitrochalcones/o-nitrocinnamaldehydesmentioning
confidence: 92%
“…In 2019, Lee et al carried out heteroannulation of 2‐nitrocinnamaldehyde 56 with thiols 57 for direct construction of 3‐thioindoles 58 with the aid of Cu(I)‐phosphene complex [71] . The reaction showed good tolerance towards 2‐nitrocinnamaldehydes and a range of alkyl, aryl, heteroaryl substituted thiol systems (61–97 % yield).…”
Section: Annulations Involving O‐nitrochalcones/o‐nitrocinnamaldehydesmentioning
confidence: 99%
“…In 2019, our group developed a new methodology for the direct construction of aryl-and heteroaryl-substituted indoles via C–N/C–S bond formation using a copper( i )-phosphine complex catalyst. 57 We found that the heteroannulation reaction of 2-nitrocinnamaldehydes 1a and thiols 85 in the presence of copper triphenylphosphine provided 3-sulfenylated indoles 86 via a sulfa-Michael addition followed by intramolecular reductive N-heteroannulation (Scheme 29). This reaction was highly tolerant to diversely substituted 2-nitrocinnamaldehydes 1a and thiols 85 bearing heterocyclic, alkyl, or aryl substituents with different electronic environments.…”
Section: Synthesis Of Indolesmentioning
confidence: 97%